Search for Lepton-Flavor-Violating Decays of Bosons With the ATLAS Detector - Davidek, Tomas; Fiorini, Luca (Frontiers in Physics, 2020)
The quest for lepton-flavour-violating processes at the LHC represents one of the key searches for new physics beyond the Standard Model. This review summarizes the direct searches for lepton-flavour-violating decays of heavy bosons with the ATLAS detector, using proton-proton collisions at the centre-of-mass energy of 13 TeV.